Indentation hardness: A simple test that correlates with the dissipated-energy predictor for fatigue-life in bovine pericardium membranes for bioprosthetic heart valves. (August 2016) - Tobaruela, Almudena; Rojo, Francisco Javier; García Paez, José María; Bourges, Jean Yves; Herrero, Eduardo Jorge; Millán, Isabel; Alvarez, Lourdes; Cordon, Ángeles; Guinea, Gustavo V.
Abstract: The aim of this study was to evaluate the variation of hardness with fatigue in calf pericardium, a biomaterial commonly used in bioprosthetic heart valves, and its relationship with the energy dissipated during the first fatigue cycle that has been shown to be a predictor of fatigue-life (García Páez et al., 2006, 2007; Rojo et al., 2010 ). Fatigue tests were performed in vitro on 24 pericardium specimens cut in a root-to-apex direction. The specimens were subjected to a maximum stress of 1 MPa in blocks of 10, 25, 50, 100, 250, 500, 1000 and 1500 cycles. By means of a modified Shore A hardness test procedure, the hardness of the specimen was measured before and after fatigue tests. Results showed a significant correlation of such hardness with fatigue performance and with the energy dissipated in the first cycle of fatigue, a predictor of pericardium durability. The study showed indentation hardness as a simple and reliable indicator of mechanical performance, one which could be easily implemented in improving tissue selection. Graphical abstract: Highlights: Hardness is a fatigue-sensitive parameter that reflects changes in early stages. Fatigue performance and energy dissipated in first cycle correlates with hardness. Hardness is proposed as an indicator of mechanical performance and fatigue-life.